Advances in taxation. Vol : 29 - Hasseldine, John (Emerald Publishing Limited, 2021)
In volume 29 of Advances in Taxation, editor John Hasseldine includes studies from expert contributors exploring topics such as: implicit taxes in imperfect markets; repatriation of indefinitely reinvested earnings; tax compliance in multiple countries; innocent spouse tax relief decisions; and the pedagogical benefits of position paper assignments in tax education. Reporting peer-reviewed research contributions from North America, Africa, and Asia, Advances in Taxation is essential reading for those looking to keep abreast of the most recent research, including empirical studies using a variety of research methods from different institutional settings and contexts.
Keywords: Taxation.; Business & Economics, Taxation -- General.; elektronické knihy; electronic books